'THE DREADFUL FLOOD OF DOCUMENTS': THE 1958 PUBLIC RECORD ACT AND ITS AFTERMATH: PART 2: AFTER-EFFECTS. Issue 134 (April 2017) - Rock, Paul
Abstract : Part 1 of this double-barrelled article described the genealogy of the 1958 Public Records Act, which was enacted at the very opening of the history of criminal justice upon which David Downes, Tim Newburn and I had embarked and which was still in force whilst we worked. It related how a concatenation of events – a prodigiously increasing accumulation of official papers generated by the swelling bureaucracy of an ever more busy state; the need for effecting economies at a time of austerity; and the application of policies driven by a new organisation and methods team at the Treasury – made it seem imperative radically to control the flow of records and restrict the numbers that were retained. Part 2 describes the implementation of the Act, the reorganisation of the Public Record Office (PRO)and the manner in which concern about what was called a 'dreadful flood of documents' continued to press hard on record retention policies.